Rehabilitation of persons with dementia: using technology to improve participation. (4th March 2021) - Zarit, Steven H.; Chiusano, Carrie; Harrison, Aime S.; Sewell, Lynne; Krause, Christopher; Liu, Yin
Abstract: Objectives: The current study examined how a technology system, "It's Never 2 Late" (iN2L), may help augment traditional rehabilitation strategies for older adults with dementia by improving engagement in therapy sessions and achieving better functional outcomes. Method: The study used a two group quasi-experimental design. Older adults with dementia (N = 96) were recruited from two rehabilitation departments housed within residential care communities. Participants received daily occupational and physical therapy sessions using treatment as usual (TAU) at one site (n = 49) or treatment with iN2L (n = 47) at the other site. A goal attainment approach was used to assess functional outcomes. It was hypothesized that patients whose therapists used iN2L in treatment will show greater attainment of therapy goals and greater engagement during OT and PT sessions than patients receiving TAU. It was also hypothesized that levels and improvement in engagement will mediate the association of treatment type (iN2L or TAU) with greater goal attainment. Results: Participants in the iN2L treatment had significantly higher goal attainment than TAU, significantly higher levels of engagement at baseline, and significantly steeper increases in engagement over the course of therapy. The effects of treatment on goal attainment was significantly mediated by increases in engagement. Conclusion: Findings suggest that iN2L technology has the potential to increase treatment engagement and enhance rehabilitation outcomes among older adults with dementia.